The Particular Expression Profiles of Circular RNA in Peripheral Blood of Myocardial Infarction Patients by RNA Sequencing - Li, Qi; Wang, Yuanyong; An, Yi; Wang, Jianxun; Gao, Yufang (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction (MI) is one of the most common illnesses seriously harmful to human health. However, the mechanisms of its pathogenesis are still not completely proved. CircRNA is one kind of non-coding RNA, recent published data suggests that circRNAs play a crucial role in heart diseases, but their expression profiles in peripheral blood of MI patients are not yet completely defined. Therefore, RNAs from peripheral bloods were recruited for high-throughput RNA-seq analysis. A total of 3862 circRNAs were detected to be remarkably changed, including 2738 circRNAs being upregulated, 1124 circRNAs being downregulated. circTMEM165, circUBAC2, circZNF609, circANKRD12, circSLC8A1 were reconfirmed by qRT-PCR in cell model. ROC curves revealed that they have good sensitivity and specificity in diagnosis of MI. Moreover, circRNAs involved in cell metabolism and function by regulating complex network among circular RNAs, microRNAs and messenger RNAs.In summary, our study depicted the particular expression profiles of circular RNA in MI patients. The results shown circRNAs may serve as a kind of ideal biomarkers for MI diagnosis. Further exploration of these circRNAs may enrich our understanding of MI etiology and progression.